Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.4103/ijmr.ijmr_1436_17
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in incidence & survival of Kaposi's sarcoma in the United States

Abstract: Background & objectives: In the United States (US), Kaposi's sarcoma (KS) is usually seen in the patients affected by human immunodeficiency virus (HIV). The racial differences in the incidence rates and survival of patients with KS have been reported in the US. We undertook this study to analyse the disparities in the race-specific incidence rate and survival of KS patients of two different races in the US based on SEER (Surveillance, Epidemiology and End Results) database. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“… 2 Kumar et al demonstrated that this trend continued for KS patients diagnosed up until 2013. 3 KS incidence continued to decline, but the decrease in the age-adjusted incidence rate (AAIR) in Black patients [annual percentage change (APC): −6.2; 95% CI: −8.8 to −3.5] was slower than that in White patients (APC: −10.9; 95% CI: −12.6 to −9.1). The hazard ratio for all-cause mortality in Black KS patients increased from 1.1 (95% CI: 1–1.2) in 1981–1995 to 1.55 (95% CI: 1.4–1.7) in 1996–2013 as compared to White patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 Kumar et al demonstrated that this trend continued for KS patients diagnosed up until 2013. 3 KS incidence continued to decline, but the decrease in the age-adjusted incidence rate (AAIR) in Black patients [annual percentage change (APC): −6.2; 95% CI: −8.8 to −3.5] was slower than that in White patients (APC: −10.9; 95% CI: −12.6 to −9.1). The hazard ratio for all-cause mortality in Black KS patients increased from 1.1 (95% CI: 1–1.2) in 1981–1995 to 1.55 (95% CI: 1.4–1.7) in 1996–2013 as compared to White patients.…”
Section: Discussionmentioning
confidence: 99%
“…The hazard ratio for all-cause mortality in Black KS patients increased from 1.1 (95% CI: 1–1.2) in 1981–1995 to 1.55 (95% CI: 1.4–1.7) in 1996–2013 as compared to White patients. 3 These racial disparities in KS incidence and outcomes may be explained by adherence to HAART treatment. HAART treatment compliance and successful HAART treatment is less likely in African American patients as compared to in non-Hispanic White patients which may result in higher rates of HIV and HHV-8 co-infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an analysis of population-based cancer incidence and survival spanning over four decades in this issue, Kumar et al 8 present trend data on racial differences in incidence of KS and survival in the United States of America highlighting the changes observed after the introduction and increasing availability of HAART. The analysis showed higher and continued incidence of KS in certain regions of USA particularly among African-Americans (AA).…”
mentioning
confidence: 99%
“…A significant limitation of the study by Kumar et al 8 was that the Surveillance, Epidemiology and End Results (SEER) database covered only a proportion of the AA and NHW populations. Hence, if there are differences between the data in SEER database and the actual real life data on KS in the health systems, estimates of incidence and survival among AA as well as NHW would have some bias.…”
mentioning
confidence: 99%